2010
DOI: 10.1038/labinvest.2010.105
|View full text |Cite
|
Sign up to set email alerts
|

Reduced transforming growth factor-β receptor II expression in hepatocellular carcinoma correlates with intrahepatic metastasis

Abstract: Hepatocellular carcinoma (HCC) occurs mainly in the liver associated with chronic hepatitis and hepatic cirrhosis as a result of prolonged viral infection. Transforming growth factor-b (TGF-b) induces the fibrosis in hepatic cirrhosis, although it is also an inhibitor of hepatocyte proliferation. To understand the role of TGF-b signaling in HCC progression, we analyzed gene expression in HCC cells in relation to TGF-b signaling using a two-way clustering algorithm. By the analysis, five HCC cell lines were cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 36 publications
4
51
0
1
Order By: Relevance
“…Recently we reported that reduced TGFBR2 expression in HCC correlated with intrahepatic metastasis [13]. Approximately 25% of HCCs showed decreased staining for TGFBR2 compared with adjacent non-cancerous hepatocytes (fig.…”
Section: Tgf-β Signaling In Hccmentioning
confidence: 96%
See 2 more Smart Citations
“…Recently we reported that reduced TGFBR2 expression in HCC correlated with intrahepatic metastasis [13]. Approximately 25% of HCCs showed decreased staining for TGFBR2 compared with adjacent non-cancerous hepatocytes (fig.…”
Section: Tgf-β Signaling In Hccmentioning
confidence: 96%
“…Indeed, the role of TGF-β signaling in HCC is controversial. Recently, we showed that reduced TGF-β receptor type II (TGFBR2) expression in HCC correlated with intrahepatic metastasis and shorter time to recurrence [13]. Various roles of TGF-β signaling may be implicated in multistep hepatocarcinogenesis.…”
Section: Molecular Alterations In Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced expression or loss of the TGFβ type I and type II receptors (TGFBR1 and TGFBR2) has been reported in various types of cancer, including HCC (23)(24)(25). TGFBR2 has been identified as the direct target of numerous miRNAs, including miR-655, miR-520c, miR-373 and miR-211 (26).…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 is also a polypeptide cytokine abundant in the liver, with high biological activity. The expression of TGF-β1 are abnormally elevated in liver cancer (49), which mainly involves the inhibition of innate immune and stimulation of Tregs generation to destroy the anti-tumor immune response, resulting in progression of malignancies (50).…”
Section: Immune Escape Mechanism Of Hccmentioning
confidence: 99%